2021
DOI: 10.1177/23247096211013230
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Ixazomib Overdose in a Patient With Multiple Myeloma

Abstract: Multiple myeloma is the second most common hematological malignancy. Ixazomib is the first oral proteasome inhibitor approved in the United States for the management of multiple myeloma who have received at least one prior treatment. The availability of oral chemotherapeutic agents for the management of multiple myeloma has made it easier for patients who do not have to come to the hospital for chemotherapy infusions. However, many barriers are associated with oral chemotherapy, and one of them is a misinterpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The primary endpoints of this study were the safety (including DLT and MTD) and the pharmacokinetics of TQB3602. DLT was defined as (1) grade ≥3 nonhematological toxicity, except grade 3 arthralgia, myalgia, and grade 3 fatigue, herpes zoster infection, and alopecia lasting <7 days, (2) grade ≥3 vomiting, diarrhea after supportive care for 5 days, (3) grade ≥3 peripheral neuropathy or grade 2 peripheral neuropathy with pain, (4) grade ≥4 hematologic toxicity, except grade 4 neutropenia and thrombocytopenia lasting <7 days, (5) platelet count <10 × 10 9 /L, (6) grade 3 thrombocytopenia with bleeding, (7) grade 3 neutropenia with fever (body temperature ≥38.5°C) or infection, or (8) any grade toxicity that the investigator determined that the participant should terminate the study. The assessment of peripheral neuropathy adhered to the standards by CTCAE 5.0, and incorporated patient-reported outcomes encompassing subjective symptoms reported by patients, as well as a thorough evaluation of instrumental activities of daily living (ADL) and self-care ADL.…”
Section: Endpointsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary endpoints of this study were the safety (including DLT and MTD) and the pharmacokinetics of TQB3602. DLT was defined as (1) grade ≥3 nonhematological toxicity, except grade 3 arthralgia, myalgia, and grade 3 fatigue, herpes zoster infection, and alopecia lasting <7 days, (2) grade ≥3 vomiting, diarrhea after supportive care for 5 days, (3) grade ≥3 peripheral neuropathy or grade 2 peripheral neuropathy with pain, (4) grade ≥4 hematologic toxicity, except grade 4 neutropenia and thrombocytopenia lasting <7 days, (5) platelet count <10 × 10 9 /L, (6) grade 3 thrombocytopenia with bleeding, (7) grade 3 neutropenia with fever (body temperature ≥38.5°C) or infection, or (8) any grade toxicity that the investigator determined that the participant should terminate the study. The assessment of peripheral neuropathy adhered to the standards by CTCAE 5.0, and incorporated patient-reported outcomes encompassing subjective symptoms reported by patients, as well as a thorough evaluation of instrumental activities of daily living (ADL) and self-care ADL.…”
Section: Endpointsmentioning
confidence: 99%
“…4,5 Ixazomib is the first boronate-based third-generation proteasome inhibitor approved for oral administration in patients with MM. [6][7][8] It suppresses the chymotrypsinlike activity of the β5 subunit of the 20S proteasome and is elective and reversible. 3 Previous clinical trials demonstrated the antitumor effect and survival benefit of ixazomib-containing regimens in RRMM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation